2012
DOI: 10.1177/1078345811420979
|View full text |Cite
|
Sign up to set email alerts
|

Nonviolent Communication Training and Empathy in Male Parolees

Abstract: The purpose of this study was to determine the impact of a behavioral intervention, nonviolent communication (NVC), on the development of empathic coping and communication skills in a sample of male parolees enrolled in substance abuse treatment (SAT; N ¼ 30). At the end of the 8-week intervention, results revealed a significant increase (p ¼ .01) in participants' empathy levels. Findings also revealed the acceptability and utility of NVC training to men on parole. Results suggest that NVC training may (a) be … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
39
1
3

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 46 publications
(46 citation statements)
references
References 35 publications
3
39
1
3
Order By: Relevance
“…Substantial research has documented the efficacy of brief behavioral interventions for increasing empathic behaviors in diverse samples including among romantic partners (Block-Lerner, Adair, Plumb, Rhatigan & Orsillo, 2007), health care providers (Heuberger, 2010), child welfare workers (Mullins, 2011), male parolees (Marlow, Nyamanthi, Grajeda, Bailey, Weber, & Younger, 2012), and prison inmates (Palusci, Crum, Bliss & Bavolek, 2008). Furthermore, brief training interventions aimed at increasing parents’ empathy towards their children have been shown to reduce harmful parenting practices and improve parent-child relationships (Akai et al, 2008; Stolk, et al, 2008; Suchman et al, 2008; Edwards, Sullivan, Meany-Walen & Kantor, 2010; Kendrick, Mulvaney, Stevens, Mytton & Stewart-Brown, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…Substantial research has documented the efficacy of brief behavioral interventions for increasing empathic behaviors in diverse samples including among romantic partners (Block-Lerner, Adair, Plumb, Rhatigan & Orsillo, 2007), health care providers (Heuberger, 2010), child welfare workers (Mullins, 2011), male parolees (Marlow, Nyamanthi, Grajeda, Bailey, Weber, & Younger, 2012), and prison inmates (Palusci, Crum, Bliss & Bavolek, 2008). Furthermore, brief training interventions aimed at increasing parents’ empathy towards their children have been shown to reduce harmful parenting practices and improve parent-child relationships (Akai et al, 2008; Stolk, et al, 2008; Suchman et al, 2008; Edwards, Sullivan, Meany-Walen & Kantor, 2010; Kendrick, Mulvaney, Stevens, Mytton & Stewart-Brown, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…Drug users on parole or probation may need assistance in managing life problems and with the transition from incarceration into the community. RDT has been found to be effective in addressing hostile or emotion-focused coping, often as a result of incarceration (Marlow et al, 2012). While at RDT sites, homeless ex-offenders are often taught coping skills designed to limit further drug use, dependence, and reduced recidivism (Marlow et al, 2012).…”
Section: Factors Associated With Ongoing Substance Abusementioning
confidence: 99%
“…For some parents, this improved their relationship with not only their child but also their partners because they responded less impulsively to stressful events. Although not many interventions for parents, including NVC training, have been studied with regard to their effects, programmes with other target groups have shown that NVC can improve empathy (Nosek et al 2014), increase emotional verbalization and reduce feelings of distress (Wacker and Dziobek 2016) and, ultimately, improve interpersonal relationships (Marlow et al 2011). The fact that parents slightly changed their attitudes and communication styles in response to this programme shows that, in relatively few sessions, the connection between parents and children, as well as between parents, can be improved.…”
Section: Discussionmentioning
confidence: 99%